Evidence for Fast Electron Transfer between the High-Spin Haems in Cytochrome bd-I from Escherichia coli. - Sergey A Siletsky; Fabrice Rappaport; Robert K Poole; Vitaliy B Borisov (PLoS ONE)
Cytochrome bd-I is one of the three proton motive force-generating quinol oxidases in the O2-dependent respiratory chain of Escherichia coli. It contains one low-spin haem (b558) and the two high-spin haems (b595 and d) as the redox-active cofactors. In order to examine the flash-induced intraprotein reverse electron transfer (the so-called ''electron backflow''), CO was photolyzed from the ferrous haem d in one-electron reduced (b5583+b5953+d2+-CO) cytochrome bd-I, and the fully reduced (b5582+b5952+d2+-CO) oxidase as a control. In contrast to the fully reduced cytochrome bd-I, the transient spectrum of one-electron reduced oxidase at a delay time of 1.5 μs is clearly different from that at a delay time of 200 ns. The difference between the two spectra can be modeled as the electron transfer from haem d to haem b595 in 3-4% of the cytochrome bd-I population. Thus, the interhaem electron backflow reaction induced by photodissociation of CO from haem d in one-electron reduced cytochrome bd-I comprises two kinetically different phases: the previously unnoticed fast electron transfer from haem d to haem b595 within 0.2-1.5 μs and the slower well-defined electron equilibration with τ ~16 μs. The major new finding of this work is the lack of electron transfer at 200 ns.